2014
DOI: 10.1111/spc3.12128
|View full text |Cite
|
Sign up to set email alerts
|

Let Go of Your (Inflated) Ego: Caring more about Others Reduces Narcissistic Tendencies

Abstract: Narcissists are known for having excessively positive self-views, but an equally defining characteristic of narcissism may be a disregard of other people. Could encouraging people to care more about others, or feel more connected to them, reduce narcissism? We describe a series of studies demonstrating that a more communal focus on others reduces narcissistic tendencies. In particular, repeating communal selfstatements (i.e., "I am a caring person"), recalling a time when one was caring, feeling empathy, focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…First, narcissists' positive view of the self implies that narcissists (a) think they are better than others (John & Robins, 1994), (b) have inflated beliefs about their skills compared to objective measures or others' ratings (Farwell & Wohlwend-Lloyd, 1998;Judge, Lepine, & Rich, 2006), (c) believe they are special and unique (Emmons, 1984;Kubarych, Deary, & Austin, 2004), and (d) have high levels of entitlement and selfishness (Campbell, Bush, Brunell, & Shelton, 2005;Miller, Price, & Campbell, 2011b). Second, narcissists tend to disregard others and are concerned with possessing agentic (e.g., competence) rather than communal (e.g., friendliness, empathy) characteristics (Jordan, Giacomin, & Kopp, 2014). Third, narcissists utilize self-enhancement strategies to regulate their self (Campbell, Hoffman, Campbell, & Marchisio, 2011).…”
Section: Advice Takingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, narcissists' positive view of the self implies that narcissists (a) think they are better than others (John & Robins, 1994), (b) have inflated beliefs about their skills compared to objective measures or others' ratings (Farwell & Wohlwend-Lloyd, 1998;Judge, Lepine, & Rich, 2006), (c) believe they are special and unique (Emmons, 1984;Kubarych, Deary, & Austin, 2004), and (d) have high levels of entitlement and selfishness (Campbell, Bush, Brunell, & Shelton, 2005;Miller, Price, & Campbell, 2011b). Second, narcissists tend to disregard others and are concerned with possessing agentic (e.g., competence) rather than communal (e.g., friendliness, empathy) characteristics (Jordan, Giacomin, & Kopp, 2014). Third, narcissists utilize self-enhancement strategies to regulate their self (Campbell, Hoffman, Campbell, & Marchisio, 2011).…”
Section: Advice Takingmentioning
confidence: 99%
“…This is because cognitive, affective, and attitudinal states have in general larger effects on behavior than their corresponding traits (e.g., Judge, Scott, & Ilies, 2006). Study 2 is also inspired by recent research suggesting that narcissism can function as a state that fluctuates across contexts and can be manipulated Jordan et al, 2014), which is based on context-dependent models of personality (Fleeson & Jayawickreme, 2015;Mischel & Shoda, 1995). As with Study 1, in Study 2 we tested Hypotheses 1 and 2.…”
Section: Studymentioning
confidence: 99%
“…Referring to the narcissism literature, there is also interesting evidence that narcissists show lower narcissism levels when contexts are more communal-oriented and/or focus on social interdependency (Jordan, Giacomin, & Kopp, 2014). Adding to that, Twenge and Campbell (2003) showed that narcissists expressed less arousal when they felt acknowledged than when they felt rejected which might be related to a reduced need to regulate oneself.…”
Section: The Narcissism In Situations Frameworkmentioning
confidence: 90%
“…Contradicting the findings of Giacomin and Jordan (2016) our results showed that positive interactions (i.e., positive disagreements, Study 2) were associated with lower levels of state narcissistic entitlement in both studies, presumably because basic needs (autonomy, relatedness, competence) and according agentic goals were met temporarily so that the positive self-views can be less enhanced or protected at this specific time point. Although speculative, this finding might be useful for future research on reductions of narcissism that often stresses the importance of triggering communal aspects in narcissists (Giacomin & Jordan, 2013;Jordan et al, 2014). Examining the "ideal constellations of needs"…”
Section: Situation-varying Variablesmentioning
confidence: 92%
See 1 more Smart Citation